Aksiologi Filsafat Pendidikan Islam Dalam Pengembangan Sistem Pendidikan Berbasis Nilai: Integrasi Tauhid, Akhlak, dan Adab - M. Masyhuri; Devi Fitri Islamiyah; Kinanti Indiarti; Abdurrahman; Siti Mahmudah Noorhayati (Prodi PAI STIT Raden Santri Gresik, 2025)
This study examines the axiological dimension of Islamic educational philosophy as a normative foundation for constructing a value-based education system. Employing library research grounded in ontological, epistemological, and axiological analysis, the study argues that core values—tauhid, ethics, adab, and maslahah—serve as essential orientations that guide all educational processes. The findings reveal that moral decline and value fragmentation in contemporary education stem from the dominance of cognitive-instrumental paradigms that detach knowledge from ethical and spiritual dimensions. In response, axiology offers a systemic framework that embeds divine values into curriculum development, pedagogical practices, assessment systems, and institutional culture. A value-based Islamic education system positions teachers as moral exemplars, the curriculum as a medium for value internalization, and evaluation as a tool for character formation. This study proposes a conceptual model that integrates tauhid as the central orientation with an ethical, transformative, and sustainable educational structure. The study concludes that holistic implementation of axiological principles strengthens learners’ spiritual identity and enhances the relevance of Islamic education in addressing the challenges of the digital era. This model provides.